Double Intervention in A Patient with Large Patent Ductus Arteriosus and Moderate Upper Muscular Ventricular Septal Defect with Bidirectional Shunt with Severe Pulmonary Hypertension (Cardiovascular Journal, 2024)
Patent ductus arteriosus (PDA) and Ventricular septal defect (VSD) are commonly encountered problems and constitute about 40% of all congenital heart lesions. The association of these two conditions in a single patient is not very uncommon. Both these conditions can be treated by placing intracardiac devices. Double interventional closure of PDA and VSD was performed in a gravely ill infant at her 3 months and 5 months of age respectively, who was suffering from recurrent pneumonia and heart failure since birth. These were lifesaving procedure for that patient which led to writing this report.Cardiovasc j 2024; 16(2): 105-109